Development and Validation of A Community-Based Prenatal Breastfeeding Mentoring Model Using Dasawisma Cadres in Indonesia - Hani Sutianingsih; Sri Achadi Nugraheni; M. Zen Rahfiludin; Yudhy Dharmawan (Journal of Universal Community Empowerment Provision, 2026)
Stunting is primarily a consequence of an environmental setback in childhood, often due to malnutrition, which has become a major public health problem in Indonesia and highly correlated with less than optimal breastfeeding behaviour. Maternal readiness during pregnancy is a key determinant of breastfeeding initiation and continuation of breastfeeding. Breastfeeding promotion in Indonesia, however, is still mainly facility-based and has not optimized community resources. This study aimed to design and assess a structured community-based prenatal breastfeeding mentoring model with dasawisma cadres. This study used a research and development design based on the Seels and Richey model, which includes analysis, design, development, validation, and implementation stages. The model and complementary materials were assessed via expert reviews as well as through a cadre and small group try-out with cadres and third-trimester pregnant women patients. All individual components of the intervention showed a high feasibility with mean scores greater than 4.21 (out of 5). The mentoring model received at least 4.67 as an average score and educational media were in the range of 4.70-4.85. This small group try-out indicated that implementation was feasible (75%), and acceptance of use among pregnant women (mean = 4.45) and cadres (mean = 4.84) was high. This model is feasible, acceptable, and appropriate for implementation at community level; Incorporating systematic prenatal mentoring into existing community structures like dasawisma represents a promising, scalable approach to improve maternal breastfeeding readiness. Further research is needed to evaluate its effectiveness on breastfeeding outcomes.